2020
DOI: 10.1177/0037549720927080
|View full text |Cite
|
Sign up to set email alerts
|

Bionic research on spikes based on the tractive characteristics of ostrich foot toenail

Abstract: Inspired by the superior fixed and traction characteristics of ostrich foot toenails, we devised, optimized and manufactured the single structure and group arrangement of a new-style bionic spike for sprint shoes to improve athletic performance. The tractive performance of the bionic spike was tested by finite element analysis and experimental verification. The optimized single structure of the bionic spike had a top slope angle of 13° and the radius of the medial groove of 7.3 mm. Compared with the convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Wang Haitao from Jilin University extracted the structure of the ostrich foot pad and established a finite-element analysis model accordingly. The modal analysis results suggested that the foot pad was mainly deformed in the form of bending at both ends, which was beneficial to protect the ostrich foot musculoskeletal system from impact damage [22]. When studying the mechanism of metatarsophalangeal joint, they also found that the ostrich metatarsophalangeal joint not only achieved compression and cushioning, but also provided energy return for forward motion [23].…”
Section: Introductionmentioning
confidence: 99%
“…Wang Haitao from Jilin University extracted the structure of the ostrich foot pad and established a finite-element analysis model accordingly. The modal analysis results suggested that the foot pad was mainly deformed in the form of bending at both ends, which was beneficial to protect the ostrich foot musculoskeletal system from impact damage [22]. When studying the mechanism of metatarsophalangeal joint, they also found that the ostrich metatarsophalangeal joint not only achieved compression and cushioning, but also provided energy return for forward motion [23].…”
Section: Introductionmentioning
confidence: 99%